The optimal threshold for α-fetoprotein and vitamin K absence or antagonist-II is still an open issue - He, Shuixiang; Hu, Junbi; Zhao, Yan (Translational Cancer Research; Vol 6, Supplement 7 (October 24, 2017): Translational Cancer Research, 2017)
Liver transplantation is an important therapy for early-stage hepatocellular carcinoma (HCC). Although patients within the Milan criteria that refer to tumor size ≤5 cm, tumor number ≤3 and no macrovascular invasion has excellent survival outcome, tumor recurrence is a major limitation of long-term survival in liver transplant patients (1,2). Currently, many centers have performed liver transplantation extended criteria beyond the Milan criteria (3).